Molecular comparison of topotypic specimens confirms Anopheles (Nyssorhynchus) dunhami Causey (Diptera: Culicidae) in the Colombian Amazon (2010)
ABSTRACT: The presence of Anopheles (Nyssorhynchus) dunhami Causey in Colombia (Department of Amazonas) is confirmed for the first time through direct comparison of mtDNA cytochrome c oxidase I (COI) barcodes and nuclear rDNA second internal transcribed spacer (ITS2) sequences with topotypic specimens of An. dunhami from Tefé, Brazil. An. dunhami was identified through retrospective correlation of DNA sequences following misidentification as Anopheles nuneztovari s.l. using available morphological keys for Colombian mosquitoes. That An. dunhami occurs in Colombia and also possibly throughout the Amazon Basin, is of importance to vector control programs, as this non-vector species is morphologically similar to known malaria vectors including An. nuneztovari, Anopheles oswaldoi and Anopheles trinkae. Species identification of An. dunhami and differentiation from these closely related species are highly robust using either DNA ITS2 sequences or COI DNA barcode. DNA methods are advocated for future differentiation of these often sympatric taxa in South America.